Buyers’ Awareness of the Traffic Light Color Coding System Introduced for Packages of Soft Drinks: A study conducted in Kekirawa Town Area - Weerasinghe, K.P.W.D.R.; Selvarajan, P. (University of Sri Jayewardenepura, 2018)
The research study aimed to investigate the Buyers’ awareness of the Traffic Light Color Coding System introduced for packages of soft drinks. According to the rises of number of diabetes cases, the Health Ministry of Sri Lanka had introduced Color Coding System for soft drink industry based on the level of sugar content. All soft drinks products have to display colors with red, amber and green according to the sugar level used by various soft drinks manufacturers. This decision has been taken by the government to educate the public and keep up the health consciousness among the citizens of Sri Lanka. This regulation had been introduced to the carbonated beverages, ready-to-serve beverages than milk based products and fruit juices. The main objective of this research is to investigate how far the buyers have the awareness of Traffic Light Color Coding System introduced for packages of soft drinks and whether buyers are concerned about the color to decide the sugar level of soft drinks when making the purchase decision. For this purpose, fifty educated buyers were selected in Kekirawa town area through the purposive sampling method and data were collected among them via personal interview method. In addition to this, the participant’s observation has also been made. The qualitative method interpretive analysis was incorporated to derive the results of the study. Findings concluded that few of the buyers had the awareness about the color coding system without knowing its meaning. But most of the buyers only know about the rule without knowing the color coding system and meaning. Findings also showed that buyers consider taste, brand name, price, ingredients, need and wants and quantity level of soft drinks than the meaning of the color coding system. Further buyers are not much concerned about their health consciousness when using soft drinks. This study suggests that a strong marketing campaign is needed to make the buyers aware of this color coding system at everywhere to implement a successful and healthy marketing practice in the country.
Keywords: Awareness; Health consciousness; Sugar level; Traffic Light Color Coding System